New Source of Rice with a Low Amylose Content and Slow In Vitro Digestion for Improved Health Benefits - Pichayaporn Srinang; Sirimaporn Khotasena; Jirawat Sanitchon; Sompong Chankaew; Sanun Jogloy; Tidarat Monkham (Agronomy, 2023)
Rice provides 70% of dietary carbohydrates and other essential nutrients. Breeding for consumer preferences and health benefits are the main considerations. Rice with a low amylose content offers a good cooking quality with its soft and sticky texture but fast starch digestibility with a high sugar release. Therefore, to provide health benefits, it is important to identify rice varieties with slow starch digestibility and a low amylose content. A total of 167 indigenous upland rice germplasms were analysed for amylose content (AC) and in vitro starch digestibility. The results showed that 167 upland rice genotypes were mostly low in AC, which was related to a soft and sticky texture during cooking. Based on the glutinous and non-glutinous types, thirteen and nine indigenous upland rice germplasms were selected with a lower AC than RD6 and KDML105 (check varieties). The in vitro starch digestibility and the hydrolysis were different at each time point and different in each variety. In the glutinous group, ULR155, ULR138, ULR308, and ULR241 released less sugar and had slower starch digestibility than RD6. In the non-glutinous group, ULR219 and ULR264 showed lower AC, slower digestion, and lower sugar release than KDML105. The results suggest that six indigenous upland rice varieties will provide a rice source to accommodate consumer preferences while also offering health benefits.